Cu AND Pb CONCENTRATIONS IN WATER COLUMN AND PLANKTON OF DOWNSTREAM SECTION OF THE MUSI RIVER - Wike Ayu Eka Putri; Anna Ida Sunaryo Purwiyanto (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
A wide range of the Musi river usage such as agricultural, forestry, industry, residential, fishing and transport activities has created a heavy metal pollution isues. This research aims to know the concentration of Cu and Pb in the water column (suspended and dissolved) and also on planktons found at downstream of Musi River. Water and plankton sampling was carried out in January and May 2015 across five research stations. Cu and Pb in water and plankton samples were analyzed using the USEPA 30050B method determined by using AAS SpektrAA plus variant with air mixure flame – acetylene. The average concentration of dissolved Cu and Pb were varied from 0.003-0.005 mgL-1and 0.002-0.004 mgL-1, respectively. A higher value was observed during the suspended phase which came to around 8.60-31.79 mgKg-1 for Cu dan 21.23-61.5 mgKg-1 for Pb. Furthermore, Cu and Pb concentration in plankton were varied from 1.046-2.430 mgKg-1 and 0.673-1.283 mgKg-1, respectively.